Kibernetska varnost v Republiki Sloveniji - previdnosti ni nikoli preveč - Abramov, Andrej (Pravnik, 2024)
The increasing importance of cyber security is becoming crucial across various sectors, from large corporations and the financial industry to small businesses and government institutions. With increasing digitisation and increasing amounts of sensitive data being transferred and stored, the need for effective cyber security measures becomes increasingly evident. Despite growing interest and demand, considerable confusion persists in the market regarding the correct approaches and solutions. Companies and organisations often face challenges in selecting appropriate technologies, implementing security strategies and complying with legislative requirements. The author explores the meaning and normative framework of cyber security, as well as the most important aspects and trends that must be taken into account when handling data. Predictions for the coming years indicate that popular operating systems, such as macOS, will become more vulnerable, and cybercriminals will continue to exploit artificial intelligence to create sophisticated attacks. Therefore, a comprehensive approach to protecting and enhancing security is needed. This approach should include raising employee awareness, deploying advanced technologies, and developing clear policies and protocols.
Keywords: artificial intelligence; cyber security; data; digitalizacija; digitisation; kibernetska varnost; NIS 2; podatki; Slovenija; UI; umetna inteligenca